MOTIVES OF CRIMINAL ACTS OF CORRUPTION IN INDONESIA - Seregig, I Ketut (Yustisia, 2018)
The data presented in this study are legal facts that come from informants who are directly involved in the investigation of corruption crime at Lampung Provincial Health Office, conducted by the High Prosecutor Attorney Lampung as well as the Prosecutor and the decision of the Panel of Judges who tried the case of corruption of Ambulance procurement project, Mobile Hospital support unit, 4 WD Ambulance sourced from APBD Lampung Province in 2013 worth of IDR 7,600,000,000.00 (seven billion six hundred million rupiah). The result of research is that corruption crime in Indonesia is done by more than one perpetrator, which is divided in two variables that support each other that is between leader and subordinate. This variable is consistent with the conclusion of Lambsdorff's research which states "there is a strong relationship between the head and subordinate in a corruption act called 'corrupt head' and 'corrupt subordinate'. Lambsdorff research results are used as a knife analysis in exploring the factors that strongly influence the occurrence of corruption in Indonesia (International Journal Elsevier, 2016). When examined from the sociological aspect, about the criminal acts of corruption that occur in Indonesia, it turns out that the perpetrators of corruption in performing acts are not alone, but more than one person, divided into 2 (two) groups, namely the superior group as the holder of power / authority and subordinate group as the executor of the activity. In this study it is found that the factors that encourage perpetrators to commit criminal acts of corruption is the existence of sociological factors, among others; factor of proximity / trust between superiors and subordinates, feelings of indebtedness of subordinates, because they have been promoted to good positions.